A critical review on extraction and refining of vanadium metal. (December 2021) - Yuan, Rui; Li, Shaolong; Che, Yusi; He, Jilin; Song, Jianxun; Yang, Bin
Abstract: Metallic vanadium has special properties and is widely used in metallurgy, aviation, nuclear industry and other fields. Vanadium is a rare and refractory metal, its high purity metal is difficult to prepare. The current mainstream extraction method is a combined process of aluminothermic reduction of vanadium oxide and electron beam smelting. Based on the properties of vanadium oxide and vanadium chloride, many researchers have also proposed various methods for the reduction of vanadium-containing precursors to prepare crude vanadium including metallothermic reduction, non-metallothermic reduction, electroreduction, and the refining of crude vanadium to produce high-purity vanadium such as molten salt electrorefining, iodide thermal decomposition, and solid state electrotransport. The review has carried out a more comprehensive summary of the various methods involved in the extraction of crude vanadium and the refining of crude vanadium, especially in recent years. The basic principles, development process, technical characteristics, and problems of corresponding methods are discussed in detail. It is expected to provide a reference for researchers and development of new extraction technologies of high-purity metallic vanadium. Highlights: The thermal reduction and electroreduction processes are introduced. The refining processes are introduced and compared.